Predicting the adsorption of -perfluorohexane in BAM-P109 standard activated carbon by molecular simulation using SAFT- Mie coarse-grained force fields - Carmelo Herdes; Esther Forte; George Jackson; Erich A Müller (Adsorption Science & Technology)
This work is framed within the Eighth Industrial Fluid Properties Simulation Challenge, with the aim of assessing the capability of molecular simulation methods and force fields to accurately predict adsorption in porous media for systems of relevant practical interest. The current challenge focuses on predicting adsorption isotherms of n -perfluorohexane in the certified reference material BAM-P109 standard activated carbon. A temperature of T = 273  K and pressures of p / p 0 = 0 . 1 , 0.3, and 0.6 relative to the bulk saturation pressure p 0 (as predicted by the model) are the conditions selected in this challenge. In our methodology we use coarse-grained intermolecular models and a top-down technique where an accurate equation of state is used to link the experimental macroscopic properties of a fluid to the force-field parameters. The state-of-the-art version of the statistical associating fluid theory (SAFT) for potentials of variable range as reformulated in the Mie group contribution incarnation (SAFT- γ Mie) is employed here. The parameters of the SAFT- γ Mie force field are estimated directly from the vapour pressure and saturated liquid density data of the pure fluids using the equation of state, and further validated by molecular dynamic simulations. The coarse-grained intermolecular potential models are then used to obtain the adsorption isotherm kernels for argon, carbon dioxide, and n -perfluorohexane in graphite slit pores of various widths using Grand Canonical Monte Carlo simulations. A unique and fluid-independent pore size distribution curve with total micropore volume of 0.5802 cm 3 /g is proposed for the BAM-P109. The pore size distribution is obtained by applying a non-linear regression procedure over the adsorption integral equation to minimise the quadratic error between the available experimental adsorption isotherms for argon and carbon dioxide and purpose-built Grand Canonical Monte Carlo kernels. The predicted adsorption levels of n -perfluorohexane at 273 K in BAM-P109 are 72.75 ± 0.01, 73.82 ± 0.01, and 75.44 ± 0.05 cm 3 /g at Standard Temperature and Pressure (STP) conditions for p / p 0 = 0 . 1 , 0.3, and 0.6, respectively.